Relationship between the biomechanical parameters technique for preliminary swings among elite hammer throwers - Rozhkov, V.; Pavlenko, V.; Okun, D.; Shutieiev, V.; Shutieieva, T.; Lenska, O. (Journal of Physical Education and Sport, 2020)
The purpose of this study was to establish the relationships between techniques of the pre-swing elite hummer throwers. The research was attended by eight hammer throwers. Measurements were taken in competitive conditions at the world Championship in 2017 (London). Biomechanical parameters were determined by processing video materials of the best attempts of hammer throw. For determine biomechanical parameters using the program Dartfish. Our results show very strong correlation between time of second pre-swing and height hammer at the first pre-swing r=-0,809, angle left knee at the second pre-swing and angle incline torso at first pre-swing r=-0,835. Strong correlation observed between angles in right knee at the first pre-swings and such parameters of techniques second pre-swings as: height lifting left heel from support r=-0,746, angle right elbow r=0,713, angle left elbow r= 0,755, height of hammer r=0,787; between angle in left knee at first pre-swing and angle in left knee r=-0,796 and height hammer at the second pre-swings; time first preliminary swing and time second preliminary swing r= 0,732. As a result correlations analysis was discovered that such parameters of the technique of the first preliminary swing as: height lifting of left heel from support, angle in right elbow, angle in left elbow, linear velocity of hammer, angular velocity of hammer, centrifugal force of hammer don't have significant impact on the technique of the second preliminary swing. Thus, the data obtained during research demonstrates importance of the, time parameters, angular parameters and height of the hammer during pre-swings for effective implementation pre-swing.